Preparing for the Death of a Loved One - Ginsberg, Robert (Journal of Scientific Exploration, 2019)
It often makes for interesting discussion whether or not knowledge of survival evidence makes one more prepared for the death of a loved one. Raw emotion will almost always win out over intellectual reasoning, so the very notion of being prepared may be nothing more than fanciful thinking. However, a recent occurrence in my life has led me to believe that knowledge and experience can lead to acceptance. After losing my fifteen year old daughter in the blink of an eye sixteen years ago, I was firmly entrenched in materialist thinking and I looked upon the suggestion of life after death as ridiculous and hurtful. I was mired in the deep chasm of despair with no hope of ever escaping the horror. Although I was apparently the recipient of what many would call striking examples of after death communications, I summarily dismissed each occurrence as coincidence. Despite the preponderance of the evidence I fought the acceptance of such a possibility for several years. Fortunately I journaled each episode and eventually sought the help of a statistician to help me calculate the odds against chance of each communication occurring. Only after seeing the hard numbers involving twenty incidents, each with odds against chance exceeding a million to one, did I relent. So, after spending the last sixteen years immersed in the investigation of survival, learning extensively about the empirical and anecdotal evidence, would I be better prepared for a future death of a loved one?